ANALISIS PENGARUH KEMAMPUAN INDIVIDU, DISIPLIN KERJA, DAN PENGALAMAN KERJA DALAM MENUNJANG KEMAJUAN ORGANISASI - Wahid Hermawan (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2022)
This study aims to find out the significance of the influence of individual abilities, work discipline and work experience on organizational progress at the Yogyakarta City Health Office. This type of research is a quantitative research method using SPSS 24. While the data collection technique in this study uses a questionnaire media with the Likert method. The population in this study were employees of the Yogyakarta city education office. The sampling technique used simple random sampling and obtained a sample of 105 employees of the Yogyakarta City Education Office. Based on the tests that have been completed in this research, the results show that: (1) individual abilities do not have a significant influence on organizational progress. (2) Work discipline has a significant effect on organizational progress. (3) Work experience has a significant effect on organizational progress. (4) Individual ability, work discipline and work experience simultaneously affect the progress of the organization.